Antipathos : Black Humor, Irony and Cynicism in Contemporary Israeli Art. - Katz-Freiman, Tami (Jerusalem : The Israel Museum, 1993)
Aya & Gal ; Ben-David, Zadok ; Ben-Shaul, Anat ; Bracha, Ram ; Cohen, Reuven ; Drumer, Ori ; Fainaru, Belu-Simion ; Ganor, Atsmon ; Gechtman, Gideon ; Hod, Nir ; Kantor, Zvika ; Katzenstein, Uri ; Lin, Hilla Lulu ; Rantzer, Philip ; Reisner, Dan ; Sack, Daniel ; Shouker, Eytan ; Siman-Tov, Naomi
biografie
Engels
boek
Keywords: Israel